2007
DOI: 10.1371/journal.ppat.0030159
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of HIV pre-mRNA Splicing as a Novel Antiretroviral Therapy to Overcome Drug Resistance

Abstract: The development of multidrug-resistant viruses compromises antiretroviral therapy efficacy and limits therapeutic options. Therefore, it is an ongoing task to identify new targets for antiretroviral therapy and to develop new drugs. Here, we show that an indole derivative (IDC16) that interferes with exonic splicing enhancer activity of the SR protein splicing factor SF2/ASF suppresses the production of key viral proteins, thereby compromising subsequent synthesis of full-length HIV-1 pre-mRNA and assembly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 42 publications
3
91
0
Order By: Relevance
“…gRNA regulation diverges from that of most cellular mRNAs, which may present novel opportunities for antiretroviral drug development. Small molecule inhibitors have been developed for SR proteins, and these have been proposed to be antiretroviral compounds, though mostly as splicing inhibitors (2,40,70). Identifying the mechanism by which SRp40/55 regulate HIV-1 Gag translation may lead to the development of specific small molecule inhibitors that inhibit HIV-1 protein production.…”
Section: Discussionmentioning
confidence: 99%
“…gRNA regulation diverges from that of most cellular mRNAs, which may present novel opportunities for antiretroviral drug development. Small molecule inhibitors have been developed for SR proteins, and these have been proposed to be antiretroviral compounds, though mostly as splicing inhibitors (2,40,70). Identifying the mechanism by which SRp40/55 regulate HIV-1 Gag translation may lead to the development of specific small molecule inhibitors that inhibit HIV-1 protein production.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of viruses on ASF/SF2 and its oncogenic potential makes ASF/SF2 an attractive target for therapy in infections and cancer. Indeed, IDC-16, a small molecule inhibitor of ASF/SF2 activity, was shown to reduce human immunodeficiency virus replication (40). Furthermore, ASF/SF2 was specifically up-regulated in a cell line model of cervical tumor progression (41), suggesting its potential as a biomarker for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, indole derivative compounds (IDCs) have been identified that selectively inhibit SR protein family members (Soret et al, 2005). Certain IDCs potently inhibited HIV-1 replication in cell culture experiments (Bakkour et al, 2007;Soret et al, 2005). Other IDCs inhibit replication of murine leukemia virus (MLV) and protect mice from MLV-induced pathogenesis (Keriel et al, 2009).…”
Section: Srp40mentioning
confidence: 99%